Occurrence of visible losses and relationship with corn silage management in dairy farms in the State of Paraná - Carvalho, Igor Quirrenbach de; Jobim, Clóves Cabreira; Osmari, Milene Puntel; Daniel, João Luiz Pratti (Acta Scientiarum. Animal Sciences, 2020)
The aim of this study was to relate the occurrence of visible losses in silage (effluent, spoiled top-layer and during feedout) with silage-making practices, physical and chemical characteristics of silage, and milk composition in Brazilian dairy herds. One-hundred and eight silos from 95 farms, in the State of Parana, were visited for data collection. Data were analyzed by Fisher’s Exact and Pearson Correlation Test. Effluent loss was higher in silages with the lowest dry matter content. Using unwalled clamp (drive-over piles) silos, neglecting a protection over the plastic film, and unloading silage with a bucket increased the occurrence of top spoilage. Feedout losses were higher in farms where: the crop was harvested with self-propelled machines; the particle size was larger, and the silage density was lower. There was no relationship between visible losses and silage composition or milk composition, except for milk fat content that, unexpectedly, there was a positive correlation with spoiled silage in the top-layer. Silage losses are reduced by adopting good practices during silage production and feedout.